Double approach for resection of anterior cranial fossa ossifying fibroma - Guevara, María; de la Fuente, Camila; Martínez Natale, Tomás; Frascarolli, Sebastián; Montilla, Flor; Mural, Miguel (Revista Argentina de Neurocirugía, 2025)
Background: the combined use of endoscopic endonasal and transcranial approaches to the ACF represents a good strategy for those cranial base lesions extending into the paranasal sinuses.Objectives: to describe step by step the surgical technique used in a double approach for the resection of an anterior cranial fossa (ACF) tumor.Case description: we present the case of an 18-year-old patient who consulted for headache, anosmia, and proptosis of the left eye. A space-occupying lesion in the ACF, calcified and compressing the left orbit with extension to the paranasal sinuses, was diagnosed.Surgery: surgical excision was decided upon using a combined transcranial and endoscopic endonasal approach. Both approaches were performed simultaneously. A bicoronal incision was made, preserving the periosteum, followed by bifrontal craniotomy and frontal sinus opening, where a lesion with bony characteristics was identified in the ACF. A linear bifrontal dural opening was made, followed by subfrontal dissection, and excision of the lesion was initiated. The ACF was communicated with the endoscopic endonasal approach. In the left nasal cavity, protrusion of the lesion was observed, and an extended left nasoseptal flap, middle turbinectomy and bilateral ethmoidectomy were performed. Draf 3b technique was utilized for access to the frontal sinus in which the frontal sinus floor is resected with additional resection of the upper nasal septum and interfrontal sinus septum. Orbital decompression was completed through resection of the papyracea lamina. Total excision of the lesion was completed, followed by reconstruction with a periosteal flap and nasoseptal flap. The patient evolved favorably, without cerebrospinal fluid leakage.Conclusion: the technique used in a combined approach for the resection of a juvenile ossifying fibroma was described, allowing for complete excision.
Keywords: Double approach; Double pedicled flap; Endoscopic endonasal; Juvenile ossifying fibroma